THE EFFECTIVENESS OF FOREIGN DEBT BASED ON SECTORS TOWARDS ECONOMIC GROWTH - Putri Indah Sugiarto; Nursini Nursini; Sri Undai Nurbayani (Kompetensi (Competence : Journal of Management Studies), 2023)
This study utilized knowledge of the utilization level of foreign loans based on economic growth areas. The metrology of foreign loan effectiveness was explained through the utilization by both the government and private sectors in foreign involvement. The primary zone was elucidated based on economic areas, while the growth percentage served as secondary and tertiary metrology of economic growth. Data was gathered through data sorting and downloading from the Central Bank's (Bank Indonesia) and Central Statistics Agency's websites. The research instrument employed was PLS SEM, with data management conducted using Smart PLS 3.0. The impact of the sectors showed a positive and significant effect on economic growth. On the other hand, the utilization of foreign loans demonstrated a significant but inverse impact on economic growth, as revealed by the output of the structural model estimation. Recommendations from the findings include expanding the production frontlines, which would be associated with an increase in the demand for services in the labor market. Additionally, the technical capabilities, particularly those aligned with the era of Society 5.0, need to be expanded and improved by job seekers. Furthermore, another suggestion involves converting short-term loan conventions into long-term periods, which would yield benefits in terms of utilization period. Finally, a recommendation is to reduce the usage of foreign loans by leveraging import mechanisms, aiming to meet the structural requirements domestically and contribute to the equitable growth of local production capacity.